PKM Pelatihan Dan Workshop Penyusunan Dan Publikasi Karya Ilmiah Untuk Meningkatkan Kemampuan Profesionalisme Guru SD Di Kecamatan Banawa Selatan - Pathuddin, Pathuddin; Linawati, Linawati; Hamid, Abd (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
The partners of this Community Partnership Program were the Elementary School Teachers Working Group ofclusters I and II, District of Banawa Selatan. Problem faced by the partners was that members of the Teachers Working Groupstill had difficulties in developing professions, writing, and publishing scientific papers, especially Classroom Action Research(CAR). The problem was including a) designing CAR implementation (determining ways of problem identification, choosingand formulation topic and title of the CAR), b) applying learning models in the CAR implementation, c) determining librarysearch techniques, d) making research instruments and data presentation techniques, determining techniques of datacollection, analysis, and interpretation in the CAR activities and e) determining CAR reporting techniques. The objective ofthis study was to improve teachers? activities in arranging scientific works, especially the Classroom Action Research that canbe taken as a way to improve teachers? professionalism compet ence. Methods used in the study were holding training andworkshop of CAR implementation, making research instruments, processing and analizing data found by the research.Furthermore, what was done was to assist partners in the preparation of and publication CAR reports and in processing CARresearch results data in the form of scientific articles and published in ISBN journals or scientific seminarsat national level.The workshop and training in the preparation and publication of scientific works were very beneficial for the TeachersWorking Group in Banawa Selatan region which had been difficult to meet the promotion requirements in the field ofscientific writing. In the application of the article preparation practice, three members of the Teachers Working Group in theBanawa SelatanDistrict have made Classroom Action Research reports, processed data and written in scientific articles